Letter - T&GWU etc Joint Committee, Woolwich, 10 May 1926 (page 1) (Woolwich)
1926-05-10 "Letter - T&GWU etc Joint Committee, Woolwich, 10 May 1926 (page 1)" [g0256001.jpg], 10 May 1926, Transport and General Workers' Union Local Organisation